The Effect of Digital Marketing and Product Quality on Customer Satisfaction with Purchase Decisions as a Moderation Variable at Cv. Carlitos Maju Pratama - Diansyah Diansyah; Putri Nadya (Return : Study of Management, Economic and Bussines, 2023)
The purpose of this study was to determine the effect of digital marketing and product quality on consumer satisfaction with purchasing decisions as a moderating variable on CV. Carlitos Maju Pratama. The population of this study are all consumers who have made purchases offline and online at CV. Carlitos Maju Pratama. The sample of this research is 236 respondents. Analysis of the data used in this study with the smart PLS method. The results of the study show: (1) Digital marketing has a positive and significant effect on consumer satisfaction (2) Product quality has a positive and significant effect on consumer satisfaction (3) Purchase decisions have a positive and significant effect on customer satisfaction (4) Moderation of purchasing decisions strengthens and is significant the influence of digital marketing on consumer satisfaction (5) Moderation of purchasing decisions strengthens and is significant for the effect of product quality and on consumer satisfaction.